Activation and tolerance of Siegesbeckia Orientalis L. rhizosphere to Cd stress - Xie, Jianyu; Xu, Xiaoxun; Zhang, Shirong; Yang, Zhanbiao; Wang, Guiyin; Li, Ting; Pu, Yulin; Zhou, Wei; Xu, Changlian; Lv, Guochun; Cheng, Zhang; Xian, Junren; et al. (Frontiers in Plant Science, 2023)
This experiment investigated the changes of rhizosphere soil microenvironment for hyperaccumulation-soil system under Cd stress in order to reveal the mechanism of hyperaccumulation and tolerance. Thus, Cd fractions, chemical compositions, and biochemical characteristics in rhizosphere soil of Siegesbeckia orientalis L. under Cd stress conditions of 0, 5, 10, 25, 50, 100, and 150 mg kg-1 were investigated through a root bag experiment, respectively. As a result, Cd induced the acidification of S. orientalis rhizosphere soil, and promoted the accumulation of dissolved organic carbon (DOC) and readily oxidizable organic carbon (ROC), which increased by 28.39% and 6.98% at the maximum compared with control. The percentage of labile Cd (acid-soluble and reducible Cd) in soil solution increased significantly (P < 0.05) from 31.87% to 64.60% and from 26.00% to 34.49%, respectively. In addition, rhizosphere microenvironment can alleviate the inhibition of Cd on soil microorganisms and enzymes compare with bulk soils. Under medium and low concentrations of Cd, the rhizosphere soil microbial biomass carbon (MBC), basal respiration, ammonification and nitrification were significantly increased (P < 0.05), and the activities of key enzymes were not significantly inhibited. This suggests that pH reduction and organic carbon (DOC and ROC) accumulation increase the bioavailability of Cd and may have contributed to Cd accumulation in S. orientalis. Moreover, microorganisms and enzymes in rhizosphere soils can enhance S. orientalis tolerance to Cd, alleviating the nutrient imbalance and toxicity caused by Cd pollution. This study revealed the changes of physicochemical and biochemical properties of rhizosphere soil under Cd stress. Rhizosphere soil acidification and organic carbon accumulation are key factors promoting Cd activation, and microorganisms and enzymes are the responses of Cd tolerance.